PENERAPAN GOOD CORPORATE GOVERNANCE, DAMPAKNYA TERHADAP PREDIKSI FINANCIAL DISTRESS PADA SEKTOR PROPERTI DAN REAL ESTATE - Cynthia Josephine (Business Accounting Review, 2013)
This study aimed to know whether the implementation of good corporate governance and financial ratios were able to predict the company experienced financial distress in the real estate and property sector listed in the Stock Exchange in the period of 2006-2011. Control variables used were the ratio of Debt To Asset, Net Profit Margin and Current Ratio. The samples used in this study were 46 property and real estate firms. The study was divided into 3 models which were Model I (1 year before the financial distress), Model II (two years before financial distress), Model III (3 years before financial distress). The hypotesis in this study was tested by using logistic regression. The results of this study proved that the model I and II, GCG score, ratio of NPM and the CR were able to predict the companies that experienced financial distress while the DTA was not able to predict the ratio of companies that experienced financial distress. While the model III, GCG score, ratio of DTA, NPM and CR were not able to predict the companies that experienced financial distress. And the accurate results was Model II.